Rab GEFs and GAPs. - Barr, F; Lambright, D (2010)
Rabs are GTP-binding proteins with conserved functions in membrane trafficking. They are regulated by a diverse group of structurally unrelated GDP-GTP exchange factors (GEFs), and a family of GTP-hydrolysis activating proteins (GAPs) containing the conserved TBC domain. Recent structural and cell biological studies shed new light on the mechanisms of Rab GEF and GAP action, and the cellular trafficking pathways they act in.